Awkward - Chmakova, Svetlana, 1979- (New York, NY : Yen Press, 2015)
After shunning Jaime, the school nerd, on her first day at a new middle school, Penelope Torres tries to blend in with her new friends in the art club, until the art club goes to war with the science club, of which Jaime is a member.
Chiefly illustrations.
"All ages."
Text in English.
Keywords: Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Clubs -- Juvenile fiction; Popularity -- Juvenile fiction; Middle schools -- Fiction; Schools -- Fiction; Clubs -- Fiction; Popularity -- Fiction; Graphic novels; Clubs; Middle schools; Popularity; Schools; Fiction; Graphic novels; Juvenile works; Graphic novels